Evaluation of changes in renal function in PARAMOUNT: a phase III study of maintenance pemetrexed plus best supportive care versus placebo plus best supportive care after induction treatment with pemetrexed plus cisplatin for advanced nonsquamous non-small-cell lung cancer. (4th May 2018) - Middleton, Gary; Gridelli, Cesare; De Marinis, Filippo; Pujol, Jean-Louis; Reck, Martin; Ramlau, Rodryg; Parente, Barbara; Pieters, Thierry; Visseren-Grul, Carla M.; San Antonio, Bélen; John, William J.; Zimmermann, Annamaria Hayden; et al.
Abstract: Objectives: To assess the effect of long-term pemetrexed maintenance therapy on patients' renal function. Methods: In the PARAMOUNT phase III trial (NCT 00789373), pemetrexed was compared with placebo as maintenance treatment in advanced nonsquamous non-small-cell lung cancer patients who completed 4 cycles of pemetrexed plus cisplatin induction therapy. To evaluate changes in renal function during pemetrexed continuation maintenance treatment, we retrospectively analyzed changes in serum creatinine (sCr), treatment-emergent adverse events, dose delays and treatment discontinuations associated with impaired renal function. Results: Creatinine clearance ≥45 mL/min was required before the start of any cycle. Patients on pemetrexed maintenance had a significantly higher percentage maximum increase in sCr over baseline versus placebo for the range of ≥10% to ≥90% increase ( p  < .05). The risk of experiencing renal events leading to dose delays and discontinuations was higher with higher increases in sCr but reversible in most patients. sCr increases of ≥30% and ≥40% were associated with gender (female), age (<70 years) and longer exposure to pemetrexed compared with placebo. Sixteen (4%) pemetrexed patients and 1 (1%) placebo patient discontinued treatment due to drug-related renal events; 13/16 (81%) of those pemetrexed patients had sCr increases ≥30% and 7/13 (54%) had pre-existing conditions and/or were receiving nephrotoxic drugs. Conclusions: The appearance of renal events leading to dose delays and/or treatment discontinuations was associated with sCr increase of at least 30%. However, it was difficult to identify patients at a higher risk of treatment discontinuation due to a drug-related renal event based only on changes in pre-maintenance laboratory values.